STUDY ON SUBSTITUTION OF Moringa Oleifera FLOUR AND BREADFRUIT FLOUR (Artocarpus altilis) IN MAKING SUPPLEMENTARY FOODS FOR PREGNANT WOMEN - Setyaningsih, Aryanti (Jurnal Teknologi Pangan dan Gizi, 2021)
This research aims to determine the organoleptic properties and nutritional value of the biskuit formulation by substituting Moringa leaf flour and breadfruit flour as a modified form of PMT biskuits for pregnant women. The breadfruit flour which has a high carbohydrate and fiber content and moringa flour have rich in iron can be used in substituting biskuits as supplementary food for pregnant women. This study used a completely randomized design with four variations of biskuit formulation with breadfruit and moringa flour substitutions, namely F0 (kontrol), F1 (20 g moringa flour: 40 g breadfruit flour), F2 (15 g moringa flour: 30 g flour. breadfruit), F3 (10 g moringa flour: 20 g breadfruit flour). Data were analyzed using ANOVA and followed by Mann Whitney at the 95% confidence level (Î±: 0.05). The results showed that difference based on the supplementary food biskuit formulation of pregnant women with Moringa leaf flour and breadfruit flour on color, aroma, texture, and taste. The results of the organoleptic test on biskuits showed that F0 was the most preferred in terms of color, taste, aroma, and texture. The higher of moringa flour and breadfruit flour substitution , the lower the overall preference for the resulting biskuits. Based on the results of the proximate biskuit test, it is known that the F1 formulation has the highest energy content, protein content, fat content, ash content, and iron content compared to other formulations. The water content and carbohydrate content of F1 formulation biskuits had the lowest levels.